Accessibility to sports performance for greater inclusiveness through robotics and artificial intelligence research - De Marco, Francesca; Brusini, Antonio (Computer methods in biomechanics and biomedical engineering, 2025)
Considering how scientific literature on the subject has been enriched with increasingly significant contributions in both sociological and organizational fields, this short essay aims to define how the use of artificial intelligence can define a valuable compensatory tool aimed at promoting greater inclusiveness in daily life activities for those in neurological deficit. In particular, we intend to focus on the benefits of sports activity in terms of increased physical and mental well-being through the use of artificial intelligence and sensors.